Triglycerides Hydrocracking Reaction of Nyamplung Oil with Non-sulfided CoMo/γ-Al2O3 Catalysts - Rismawati Rasyid; Rahmaniah Malik; Heri Septya Kusuma; Achmad Roesyadi; Mahfud Mahfud (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
The purpose of this research are to study the temperature influence in hydrocracking process of the nyamplung oil (Calophyllum inophyllum) using a non-sulfided CoMo/γ-Al2O3 catalyst and to develop a simple kinetic model in interpreting the data of hydrocracking products. The experiment was carried out in a pressurized batch reactor operated pressure up 30 bar. The CoMo catalyst supported with γ-Al2O3 was prepared through impregnation method without sulfidation process. The operating temperature varied from 200 to 350 oC. The results show that the non-sulfided CoMo/γ-Al2O3 catalysts, nyamplung oil triglycerides can converted into gasoil and gasoline-like hydrocarbons. The triglyceride hydrocracking reaction of nyamplung oil followed a several stages, i.e., hydrogenation, dehydrogenation, and cracking. Based on the compounds contained in liquid product, hydrocracking reaction was dominated by decarboxylation. The products obtained in hydrocracking process of nyamplung oil are classified to gasoil (C11-C18) and gasoline (C5-C10).  The triglycerides hydrocracking reaction of nyamplung oil was assumed by following a series reaction mechanism and a simple kinetic model used for determined the kinetics constants. The highest reaction conversion is 99.10% obtained at temperature of 350 °C for 160 minutes reaction time.